Hepatitis C: evaluation of outcomes and georeferencing of cases in Santa Cruz do Sul, Brazil, between 2002 and 2015. A cross-sectional study - Possuelo, Lia Goncalves; Perin, Daiane; Breunig, Patricia Faber; Schroeder, Daniel Felipe; Allgayer, Manuela Filter; Darsie, Camilo; Carneiro, Marcelo; Hermes, Vanda (São Paulo Medical Journal, 2018)
BACKGROUND: Hepatitis C virus infection is one of the main causes of chronic liver disease, with high death rates. The aim here was to analyze case outcomes, sociodemographic and clinical characteristics and spatial distribution among patients diagnosed with hepatitis C in the city of Santa Cruz do Sul (RS), Brazil. DESIGN AND SETTING: Cross-sectional study on 200 cases of hepatitis C in Santa Cruz do Sul that were notified between 2002 and 2015. METHODS: Secondary data including sociodemographic and clinical variables and type of outcome (death, follow-up, abandonment or clinical cure) were gathered. The spatial distribution analysis on hepatitis C virus cases according to outcome was based on information regarding residential address. RESULTS: 58.5% of the patients were 41 years of age and over, 67% were males and 92.5% had the chronic form of the disease. The most frequent transmission route was illicit drug injection (29%); 15.1% of the patients presented coinfection with the human immunodeficiency virus (HIV). Regarding outcomes, 31% achieved clinical cure, 10% died and 20% abandoned follow-up. The cases studied were mainly located in regions of the city characterized by lower socioeconomic status, with high frequency of places used for drug trafficking. CONCLUSION: The population consisted of adults aged 41 years and over, mostly with chronic hepatitis C. The most common transmission routes were illicit drug injection and blood transfusions. There were high rates of HIV coinfection and abandonment of disease monitoring and predominance of cases in neighborhoods with low socioeconomic status.